Lithium ion positive electrode material, preparation method thereof and lithium ion battery

By introducing a carbon coating layer into lithium iron phosphate materials and controlling its lattice structure and polarization characteristics, the problem of poor lithium ion diffusion is solved and the DCR performance of lithium-ion batteries is significantly improved.

CN119361657APending Publication Date: 2025-01-24XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411622545.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Due to the one-dimensional lithium iron phosphate diffusion channel of lithium ions, lithium ions have slow motion speed and short diffusion distance, which has problems such as low electronic conductivity and poor diffusion of lithium ions, which affect the DCR performance, rate performance and low temperature performance of the battery.

Method used

By introducing carbon coating layers in lithium ion positive materials, and through high -pressure water thermal reactions and high -temperature sintering, control the lattice structure and polarization characteristics of the material, so that the size of the crystal surface of the XRD spectrum (200) ) The ratio of crystal surface size KR is within the range of 0.82 ~ 1.08, and the time domain differential potential ratio KΔV is within the range of 2.21 to 3.2.

Benefits of technology

Effectively improve the speed and diffusion distance of lithium ion positive materials in the internal lithium ion, optimize the level of the material, significantly improve the DCR performance of the battery, and has a good practical application prospect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361657A_ABST
    Figure CN119361657A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium batteries, and discloses a lithium ion positive electrode material, a preparation method thereof and a lithium ion battery. The lithium ion positive electrode material provided by the invention comprises a lithium iron phosphate material with a carbon coating layer, the ratio Kr of the (200) crystal face size to the (101) crystal face size in an XRD spectrogram of the lithium ion positive electrode material is 0.82-1.08, and the time domain differential potential ratio K delta V of a battery prepared from the lithium ion positive electrode material is 2.21-3.2. A Kr value in an XRD (X-Ray Diffraction) spectrogram of the lithium ion positive electrode material is within a specific range value, and a time domain differential potential ratio K [delta] V of a battery prepared from the lithium ion positive electrode material is also within a specific range value; the problem that the polarization phenomenon in the material is enhanced due to the fact that lithium ions in the lithium iron phosphate material cannot migrate in time in the charging and discharging process of the battery can be effectively solved, so that the power or energy storage battery prepared by taking the lithium iron phosphate material as the positive electrode material has excellent DCR performance, and the application prospect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium ion positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have been gradually widely used in various industries since 1991, and have developed rapidly in recent years. In addition to their applications in 3C products such as mobile phones and laptops, the development of electric vehicles and smart grid energy storage has put forward new demands and technical requirements for secondary batteries.

[0003] Lithium iron phosphate cathode materials are stable and not easy to decompose, and the batteries made of them have safety that other cathode material systems cannot match. In addition, lithium iron phosphate batteries also have the advantages of long cycle life, abundant resources and low cost, and are the focus of research and industrial development in the field of power and energy storage lithium-ion batteries.

[0004] However, compared with the layered transition metal oxide structure of traditional positive electrode materials, lithium iron phosphate materials have an olivine structure, and the lithium ion diffusion channel is one-dimensional. The lithium ions move slowly and diffuse over a short distance in the bulk phase of the material, resulting in low electronic conductivity and poor lithium ion diffusion. During the battery charge and discharge process, the lithium ions inside the lithium iron phosphate material cannot migrate in time, and the internal polarization of the material is enhanced, which has a significant adverse effect on the DCR performance of power or energy storage batteries and the closely related rate performance and low-temperature performance, hindering the practical application of lithium iron phosphate positive electrode materials and having significant limitations. Summary of the invention

[0005] The first object of the present invention is to provide a lithium ion positive electrode material. In the lithium ion positive electrode material, the ratio Kr of the (200) crystal plane size to the (101) crystal plane size in the XRD spectrum is within a specific range, and the time domain differential potential ratio Kr of the battery prepared from the lithium ion positive electrode material is ΔV It is also within a specific range of values. Through the special selection of specific parameters of the lithium-ion positive electrode material, it can effectively solve the problem of enhanced internal polarization of the material due to the inability of lithium ions in the lithium iron phosphate material to migrate in time during the battery charging and discharging process. As a result, the power or energy storage battery prepared with it as the positive electrode material has excellent DCR performance and good application prospects.

[0006] The second purpose of the present invention is to provide a method for preparing a lithium ion positive electrode material.

[0007] The third object of the present invention is to provide a lithium ion battery.

[0008] Specifically, the lithium ion positive electrode material provided by the present invention includes a lithium iron phosphate material having a carbon coating layer, and the lithium ion positive electrode material has the following characteristics: the ratio Kr of the (200) crystal plane size to the (101) crystal plane size in the XRD spectrum of the lithium ion positive electrode material is 0.82 to 1.08;

[0009] and, the time domain differential potential ratio K of the battery made of the lithium ion positive electrode material ΔV is 2.21~3.2, and K ΔV The calculation formula is as follows:

[0010]

[0011] Among them, V0 is the open circuit potential value measured by the battery, V 1s V is the potential value of the battery measured 1s after constant current is applied. 18s K is the potential value measured by the battery 18s after constant current is applied; ΔV The test conditions include temperature of 24-26°C and constant current of 0.09-0.11°C.

[0012] Furthermore, in the XRD spectrum of the lithium-ion positive electrode material, the ratio Kr of the (200) crystal plane size to the (101) crystal plane size is 0.82 to 1.03.

[0013] Furthermore, the time domain differential potential ratio K of the battery made of the lithium ion positive electrode material is ΔV It is 2.24~3.15.

[0014] Furthermore, the lithium ion positive electrode material comprises a lithium iron phosphate material having a carbon coating layer, and the general chemical formula of the lithium iron phosphate material comprises LiFe x M 1-x PO4; wherein 0.98≤x<1.0; the M element is selected from one or more of Mn, F, Al, Ti, Zr, Co, Zn and V.

[0015] Furthermore, based on the BET area of ​​the lithium iron phosphate material, the carbon content of the carbon coating layer in the lithium ion positive electrode material is 7.5 to 13 g / m 2 .

[0016] The preparation method of the above-mentioned lithium ion positive electrode material provided by the present invention comprises: S1, taking a lithium source, an iron source, a phosphorus source, an orientation regulator and a solvent for mixing treatment I to obtain a premixed slurry; taking the premixed slurry for high-pressure hydrothermal reaction and purification treatment to obtain lithium iron phosphate slurry; S2, taking the lithium iron phosphate slurry, a carbon source and a lithium supplement agent for mixing treatment II and drying treatment to obtain a mixed dry powder; S3, taking the mixed dry powder for high-temperature sintering to obtain the lithium ion positive electrode material; wherein the orientation regulator includes one or more of tetracarboxyl porphyrin, sucrose, starch, acetic acid, oxalic acid, citric acid, sodium dodecylbenzene sulfonate, glucoside and polyethylene glycol sulfate, and the addition concentration of the orientation regulator is 0.4-10wt% based on the total mass of the lithium source and the lithium supplement agent.

[0017] Furthermore, in step S1, based on the mass of the lithium source, the alignment regulator includes 0.009-0.011 wt% of tetracarboxyl porphyrin, 0.049-0.051 wt% of starch, 0.29-0.31 wt% of acetic acid and 0.09-0.11 wt% of glucoside in an added concentration.

[0018] Furthermore, in step S1, based on the mass of the lithium source, the alignment regulator includes oxalic acid at a concentration of 2.9-3.1 wt%, citric acid at a concentration of 0.9-1.1 wt%, and polyethylene glycol sulfate at a concentration of 0.049-0.051 wt%.

[0019] Furthermore, in step S1, based on the mass of the lithium source, the alignment regulator includes 0.009-0.011 wt% of tetracarboxyl porphyrin, 4.9-5.1 wt% of oxalic acid, 0.9-1.1 wt% of citric acid and 0.9-1.1 wt% of sodium dodecylbenzene sulfonate.

[0020] Furthermore, in step S1, the lithium source is selected from lithium carbonate and / or lithium hydroxide.

[0021] Furthermore, in step S1, the iron source is selected from one or more of ferrous oxalate, ferrous nitrate and ferrous sulfate.

[0022] Furthermore, in step S1, the phosphorus source is phosphoric acid.

[0023] Furthermore, in step S1, the solvent is selected from one or more of ethylene glycol, diethylene glycol and water.

[0024] Furthermore, in step S1, the molar ratio of lithium element, iron element and phosphorus element added in the lithium source, iron source and phosphorus source is (2.98-3.02):1:(0.97-1.03).

[0025] Furthermore, a supplement containing an M element is added to the mixing treatment I, and the M element is selected from one or more of Mn, F, Al, Ti, Zr, Co, Zn and V.

[0026] Furthermore, the supplement containing the M element is selected from one or more of manganese sulfate, aluminum fluoride, titanium oxalate, zirconium sulfate, cobalt sulfate, zinc chloride and vanadium sulfate.

[0027] Furthermore, in step S1, the molar ratio of lithium element to M element in the lithium source and the supplement is 1:(0.005-0.025).

[0028] Furthermore, in step S1, the gas pressure of the high-pressure hydrothermal reaction is 1.6-2 MPa, the temperature is 180-230° C., and the time is 2-5 h.

[0029] Furthermore, in step S2, the carbon source is selected from one or more of glucose, sucrose, starch, and polyvinyl alcohol.

[0030] Furthermore, in step S2, the lithium supplement is selected from one or more of lithium carbonate, lithium hydroxide, lithium oxide, lithium gluconate, lithium citrate, lithium dihydrogen phosphate and lithium phosphate.

[0031] Furthermore, in step S2, based on the dry weight of lithium iron phosphate in the lithium iron phosphate slurry, the added amount of the carbon source is 1-20wt%, and the added amount of the lithium supplement agent is 1-4wt%.

[0032] Furthermore, in step S3, the high temperature sintering atmosphere includes an inert gas and optionally carbon monoxide, the temperature is 650-780° C., and the time is 3-10 hours.

[0033] The lithium ion battery provided by the present invention comprises the above-mentioned lithium ion positive electrode material.

[0034] Beneficial effects:

[0035] The lithium ion positive electrode material provided by the present invention has a lithium iron phosphate material with a carbon coating layer, and the ratio Kr of the (200) crystal plane size to the (101) crystal plane size in the XRD spectrum thereof is within a specific numerical range of 0.82 to 1.08, so that the lithium ion positive electrode material has a specific microscopic crystal structure and special macroscopic morphological characteristics, thereby optimizing the phase change process of the positive electrode material morphology and crystal plane distribution during charging and discharging; at the same time, the time domain differential potential ratio K of the battery prepared by the lithium ion positive electrode material measured under the temperature condition of 24 to 26°C is ΔVIn the specific numerical range of 2.21 to 3.2, it has a special ratio of bulk and interface polarization, thereby effectively optimizing the total polarization level of the positive electrode material, and simultaneously optimizing multiple factors such as the material structure, phase change process, and polarization level. Through the coordinated cooperation of the above multiple factors, the movement speed and diffusion distance of lithium ions inside the lithium ion positive electrode material are improved, thereby effectively solving the problems of low electronic conductivity and poor lithium ion diffusion caused by the structural characteristics of the existing lithium iron phosphate material; the battery made of the lithium ion positive electrode material has a well-improved DCR performance compared to traditional lithium iron phosphate batteries, and has good practical application prospects.

[0036] In some specific embodiments, a preparation method of the above-mentioned lithium ion positive electrode material is also provided, in which an orientation regulator is introduced into a high-pressure hydrothermal reaction, and the difference in the adsorption capacity of different crystal faces to the orientation regulator is utilized to control the crystal face growth to achieve directional regulation of the crystal face orientation, thereby obtaining a lithium ion positive electrode material with specific Kr and K ΔV Value of lithium-ion cathode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a graph showing the experimental results of the DCR performance test of the lithium-ion positive electrode material provided in Test Example 3 of the present invention. DETAILED DESCRIPTION

[0038] Based on the problems of low electronic conductivity and poor lithium ion diffusion in existing lithium iron phosphate materials, the inventors of the present invention have creatively discovered through extensive and in-depth research that the organic adjustment of multiple factors such as the structure, phase change process and polarization level of the material can effectively solve the problems of low electronic conductivity and poor lithium ion diffusion caused by the structural characteristics of the existing lithium iron phosphate materials. Based on this, the lithium ion positive electrode material provided by the present invention is obtained.

[0039] In the present invention, the lithium ion positive electrode material comprises a lithium iron phosphate material having a carbon coating layer, and the lithium ion positive electrode material has a special lattice structure and a ratio of bulk phase and interface polarization.

[0040] In the present invention, the special lattice structure of the lithium ion positive electrode material specifically includes: in the XRD spectrum, the ratio Kr of the (200) crystal plane size to the (101) crystal plane size of the lithium ion positive electrode material is 0.82 to 1.08, such as 0.82, 0.8213, 0.8740, 1.0268, 1.08 or any value therebetween.

[0041] In some specific embodiments, in the XRD spectrum of the lithium ion positive electrode material, the ratio Kr of the (200) crystal plane size to the (101) crystal plane size is preferably 0.82 to 1.03. In this case, the battery made of the lithium ion positive electrode material has a better DCR performance.

[0042] In the present invention, the ratio of the special bulk phase and interface polarization of the lithium ion positive electrode material specifically includes: the time domain differential potential ratio K of the battery made of the lithium ion positive electrode material ΔV is 2.21~3.2, and K ΔV The calculation formula is as follows:

[0043]

[0044] Among them, V0 is the open circuit potential value measured by the battery, V 1s V is the potential value of the battery measured 1s after constant current is applied. 18s is the potential value measured by the battery 18s after the constant current is applied. More specifically, the time domain differential potential ratio K ΔV The test conditions specifically include: a temperature of 24 to 26°C, such as 24°C, 24.31°C, 24.65°C, 24.999°C, 25°C, 25.001°C, 25.13°C, 25.5°C, 26°C or any value therebetween; a constant current of 0.09 to 0.11C, such as 0.09C, 0.093C, 0.095C, 0.1C, 0.101C, 0.108C, 0.11C or any value therebetween.

[0045] In some specific embodiments, the time domain differential potential ratio K of the battery made of the lithium ion positive electrode material is ΔV Preferably, it is 2.24 to 3.16. In this case, the battery made of the lithium ion positive electrode material has a more excellent DCR performance.

[0046] In the present invention, the lithium iron phosphate material included in the lithium ion positive electrode material is a type of positive electrode material used in lithium ion battery materials. Those skilled in the art can select from existing materials according to actual needs, and the present invention does not impose any special restrictions on it. That is, the specific material composition of the lithium ion positive electrode material does not limit the protection scope of the present invention. The lithium ion positive electrode materials including the lithium iron phosphate material with a carbon coating layer obtained by adjusting the lattice structure of the material and the ratio of bulk phase and interface polarization within the above range all fall within the protection scope of the present invention.

[0047] In some specific embodiments, in the lithium ion positive electrode material, the chemical formula of the lithium iron phosphate material preferably includes: LiFe x M 1-xPO4. Wherein, 0.98≤x<1.0; M element is selected from one or more of Mn, F, Al, Ti, Zr, Co, Zn and V. At this time, the incorporation of M element enables more active sites to be formed inside the material, thereby further optimizing the relevant properties of the lithium ion positive electrode material.

[0048] In some specific embodiments, based on the BET area of ​​the lithium iron phosphate material, the carbon content of the carbon coating layer in the lithium ion positive electrode material is preferably 7.5 to 13 g / m 2 , such as 7.5g / m 2 , 7.8g / m 2 , 8.0g / m 2 , 8.5g / m 2 , 9.0g / m 2 , 9.5g / m 2 , 10.0g / m 2 10.5g / m 2 , 11.0g / m 2 , 11.5g / m 2 , 12g / m 2 , 13g / m 2 Or any value therebetween. At this time, the carbon coating of the positive lithium ion material is better, so that the battery made therefrom has a better DCR performance.

[0049] Based on the purpose of obtaining the above-mentioned lithium ion positive electrode material, the present invention also provides a preparation method of lithium ion positive electrode material. The preparation method specifically comprises: S1, taking a lithium source, an iron source, a phosphorus source, an orientation regulator and a solvent for mixing treatment I to obtain a premixed slurry; taking the premixed slurry for high pressure hydrothermal reaction and purification treatment to obtain lithium iron phosphate slurry; S2, taking the lithium iron phosphate slurry, a carbon source and a lithium supplement agent for mixing treatment II and drying treatment to obtain a mixed dry powder; S3, taking the mixed dry powder for high temperature sintering to obtain the lithium ion positive electrode material.

[0050] In the present invention, step S1 is a key step in preparing the above-mentioned lithium ion positive electrode material - using a high-pressure hydrothermal method and introducing an orientation regulator, using the difference in the adsorption capacity of different crystal faces to the orientation regulator, controlling the crystal face growth to achieve directional regulation of the crystal face orientation, thereby obtaining a material with specific Kr and K ΔV (25℃) value of lithium-ion positive electrode materials.

[0051] In the present invention, in step S1, specific examples of the alignment regulator include but are not limited to: one or more of tetracarboxyl porphyrin, sucrose, starch, acetic acid, oxalic acid, citric acid, sodium dodecylbenzene sulfonate, glucoside and polyethylene glycol sulfate. More specifically, based on the mass of the lithium source, the added concentration of the alignment regulator is preferably 0.4-10wt%, such as 0.4wt%, 0.48wt%, 0.5wt%, 1wt%, 1.3wt%, 4.05wt%, 7.01wt%, 10wt% or any value therebetween.

[0052] In some specific embodiments, in step S1, based on the mass of the lithium source, the orientation regulator preferably includes: adding tetracarboxyl porphyrin at a concentration of 0.009-0.011wt%, such as 0.009wt%, 0.0093wt%, 0.0095wt%, 0.01wt%, 0.0103wt%, 0.0108wt%, 0.011wt% or any value therebetween; adding starch at a concentration of 0.049-0.051wt%, such as 0.049wt%, 0.0493wt%, 0.0495wt% , 0.05wt%, 0.0508wt%, 0.051wt% or any value therebetween; adding acetic acid at a concentration of 0.29-0.31wt%, such as 0.029wt%, 0.0295wt%, 0.03wt%, 0.0305wt%, 0.31wt% or any value therebetween; and adding glucoside at a concentration of 0.09-0.11wt%, such as 0.09wt%, 0.093wt%, 0.098wt%, 0.1wt%, 0.105wt%, 0.11wt% or any value therebetween. At this time, the Kr value of the prepared lithium ion positive electrode material is 0.82-0.83, K ΔV The DCR of the battery made of the lithium-ion positive electrode material is 2.2-2.3, and the battery has excellent DCR performance.

[0053] In some specific embodiments, in step S1, based on the mass of the lithium source, the orientation regulator preferably includes: adding oxalic acid at a concentration of 2.9-3.1wt%, such as 2.9wt%, 2.93wt%, 2.96wt%, 3wt%, 3.08wt%, 3.1wt% or any value therebetween; adding citric acid at a concentration of 0.9-1.1wt%, such as 0.9, 0.93, 0.94, 0.97, 1, 1.07, 1.1 or any value therebetween; and adding polyethylene glycol sulfate at a concentration of 0.049-0.051wt%, such as 0.049wt%, 0.0495wt%, 0.05wt%, 0.0505wt%, 0.051wt% or any value therebetween. At this time, the Kr value of the prepared lithium ion positive electrode material is 0.87-0.88, K ΔV The DCR of the battery made of the lithium-ion positive electrode material is 2.6-2.7, and the battery has excellent DCR performance.

[0054] In some specific embodiments, in step S1, based on the mass of the lithium source, the orientation regulator preferably includes: adding tetracarboxyl porphyrin at a concentration of 0.009-0.011wt%, such as 0.009wt%, 0.0095wt%, 0.01wt%, 0.0105wt%, 0.011wt% or any value therebetween; adding oxalic acid at a concentration of 4.9-5.1wt%, such as 4.9wt%, 4.93wt%, 4.95wt%, 5wt% , 5.05wt%, 5.1wt% or any value therebetween; adding citric acid at a concentration of 0.9-1.1wt%, such as 0.9, 0.91, 0.95wt%, 1wt%, 1.03wt%, 1.08wt%, 1.1wt% or any value therebetween; and, adding sodium dodecylbenzene sulfonate at a concentration of 0.9-1.1wt%, such as 0.9wt%, 0.95wt%, 1wt%, 1.05wt%, 1.1wt% or any value therebetween. At this time, the Kr value of the prepared lithium ion positive electrode material is 1.0-1.1, and K ΔV The DCR performance of the battery made of the lithium-ion positive electrode material is excellent.

[0055] In the present invention, in step S1, the lithium source is a type of reagent commonly used in the preparation of existing lithium iron phosphate materials, and the present invention does not impose any special limitation on it. Specific examples thereof include but are not limited to: lithium carbonate and / or lithium hydroxide.

[0056] In the present invention, in step S1, the iron source is a type of reagent conventionally used in the preparation of existing lithium iron phosphate materials, and the present invention does not impose any particular limitation on it. Specific examples thereof include but are not limited to: one or more of ferrous oxalate, ferrous nitrate and ferrous sulfate.

[0057] In the present invention, in step S1, the phosphorus source is a type of reagent commonly used in the preparation of existing lithium iron phosphate materials, and the present invention does not impose any particular limitation on it. Specific examples thereof include but are not limited to: phosphoric acid.

[0058] In the present invention, in step S1, the solvent is a type of reagent commonly used in the preparation of existing lithium iron phosphate materials, and the present invention does not impose any special limitation on it. Specific examples thereof include but are not limited to: one or more of ethylene glycol, diethylene glycol and water.

[0059] In some specific embodiments, in step S1, the molar ratio of lithium, iron and phosphorus in the lithium source, iron source and phosphorus source is preferably (2.98-3.02):1:(0.97-1.03), such as 2.98:1:0.97, 3:1:0.97, 3.02:1:0.97, 2.98:1:1, 3:1:1, 3.02:1:1, 2.98:1:1.03, 3:1:1.03, 3.02:1:1.03 or any value therebetween.

[0060] In the present invention, in step S1, the mixing treatment I is a type of technical means commonly used in the prior art for uniformly mixing materials. Those skilled in the art can make adaptive choices based on actual needs. Specific examples include but are not limited to: one or more of emulsification mixing, ultrasonic mixing and mechanical mixing.

[0061] In some specific embodiments, in step S1, the mixing treatment I is preferably emulsified mixing. At this time, emulsified mixing can effectively achieve sufficient mixing of the lithium source, iron source, phosphorus source, orientation regulator and solvent, which is conducive to the high-pressure hydrothermal reaction.

[0062] In some specific embodiments, in step S1, a supplement containing an element M is preferably added to the mixing process I. The element M can be completely identical, partially identical, or completely different from the element M in the chemical formula of the lithium iron phosphate material, and specific examples thereof include but are not limited to: one or more of Mn, F, Al, Ti, Zr, Co, Zn, and V. More specifically, specific examples of the supplement containing an element M include but are not limited to: one or more of manganese sulfate, aluminum fluoride, titanium oxalate, zirconium sulfate, cobalt sulfate, zinc chloride, and vanadium sulfate.

[0063] In some preferred embodiments, the molar ratio of lithium element to M element in the lithium source and the supplement is preferably 1:(0.005-0.025), such as 1:0.005, 1:0.01, 1:0.015, 1:0.02, 1:0.025 or any value therebetween.

[0064] In some specific embodiments, in step S1, the conditions of the high-pressure hydrothermal reaction specifically include: the gas pressure is preferably 1.6-2MPa, such as 1.6MPa, 1.7MPa, 1.8MPa, 1.9MPa, 2.0MPa or any value therebetween; the temperature is preferably 180-230°C, such as 180°C, 183°C, 185°C, 190°C, 195°C, 200°C, 220°C, 230°C or any value therebetween; the time is preferably 2-5h, such as 2h, 2.3h, 2.8h, 3h, 3.5h, 4h, 5h or any value therebetween. At this point, the above-mentioned high-pressure hydrothermal reaction conditions are conducive to the control of crystal face growth, thereby achieving a better crystal face orientation regulation effect.

[0065] In the present invention, in step S1, the purification treatment is a technical means conventionally used in the preparation of existing lithium iron phosphate materials to remove other impurities in lithium iron phosphate slurry. Those skilled in the art can make adaptive choices according to actual needs, and the present invention does not impose any special limitation on it.

[0066] In the present invention, in step S2, the carbon source is a type of reagent that can provide carbon atoms for the formation of the carbon coating layer, and specific examples thereof include but are not limited to: one or more of glucose, sucrose, starch, and polyvinyl alcohol.

[0067] In the present invention, in step S2, the lithium supplement agent is a type of reagent commonly used in the preparation of existing lithium iron phosphate materials. The present invention does not impose any special limitation on it. Specific examples thereof include but are not limited to: one or more of lithium carbonate, lithium hydroxide, lithium oxide, lithium gluconate, lithium citrate, lithium dihydrogen phosphate and lithium phosphate.

[0068] In some specific embodiments, in step S2, based on the dry weight of lithium iron phosphate in the lithium iron phosphate slurry, the amount of the carbon source added is preferably 1-20wt%, such as 1wt%, 1.5wt%, 2wt%, 5wt%, 8wt%, 10wt%, 15wt%, 20wt% or any value therebetween; the amount of the lithium supplement agent added is preferably 1-4wt%, such as 1wt%, 1.3wt%, 1.8wt%, 2wt%, 2.5wt%, 3wt%, 4wt% or any value therebetween. At this time, the use of the above-mentioned carbon source and the amount of lithium supplement agent added can optimize the formation process of the carbon coating layer in the subsequent high-temperature sintering, thereby obtaining a lithium ion positive electrode material with better performance.

[0069] In the present invention, in step S2, the mixing treatment II is a type of technical means commonly used in the prior art for uniformly mixing materials. Those skilled in the art can make adaptive choices based on actual needs. Specific examples include but are not limited to: ultrasonic mixing and / or mechanical mixing.

[0070] It should be noted that the "I" and "II" in the mixing treatment I and mixing treatment II described in the present invention are only for the convenience of description and do not have any special limiting effect.

[0071] In the present invention, in step S2, the drying treatment is a technical means conventionally used in the prior art to remove solvents from materials to form dry powders. Those skilled in the art can make adaptive choices based on actual needs, and specific examples include but are not limited to: spray drying.

[0072] In some specific embodiments, in step S3, the conditions for high temperature sintering specifically include: the atmosphere preferably includes an inert gas and optional carbon monoxide; the temperature is preferably 650-780°C, such as 650°C, 658°C, 670°C, 700°C, 750°C, 780°C or any value therebetween; the time is preferably 3-10h, such as 3h, 3.8h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or any value therebetween.

[0073] Based on the excellent performance of the above lithium ion positive electrode material, the present invention also provides a lithium ion battery. The lithium ion battery includes the above lithium ion positive electrode material.

[0074] In the present invention, lithium-ion batteries are a conventional type of device in the technical field of lithium batteries, and the present invention does not impose any particular limitation on their specific structure, reagents, and sizes.

[0075] Embodiments of the present invention are described in detail below, and the examples of the embodiments are intended to be used to explain the present invention, but should not be construed as limiting the present invention. In the embodiments, if specific techniques or conditions are not specified, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not specified for reagents or instruments used, they are all conventional products that can be obtained commercially.

[0076] Examples 1 to 3

[0077] Examples 1 to 3 are used to illustrate a lithium ion positive electrode material and a preparation method thereof. The preparation of the lithium ion positive electrode material specifically includes:

[0078] S1. Take lithium hydroxide as a lithium source, ferrous sulfate as an iron source, phosphoric acid as a phosphorus source and an appropriate amount of ethylene glycol as a solvent, add the above substances and an orientation regulator into an emulsifier for emulsification and mixing to obtain a premixed slurry; take the premixed slurry and add it into a high-pressure reactor, carry out a high-pressure hydrothermal reaction at 1.8 MPa and 200°C for 3.5 hours to obtain a mixed slurry of lithium iron phosphate and by-products; take the mixed slurry, filter it and wash it with a 10% ethylene glycol-water mixture, and then add an appropriate amount of water again to stir evenly to obtain a lithium iron phosphate slurry.

[0079] S2. Mix the lithium iron phosphate slurry, the carbon source and the lithium supplement agent, stir them evenly and then spray dry them to obtain a mixed dry powder.

[0080] S3, taking the mixed dry powder and adding it into a sintering furnace, performing high-temperature sintering at 730° C. for 7 hours, and performing gas crushing on the material obtained by the high-temperature sintering to obtain the lithium ion positive electrode material.

[0081] The specific preparation conditions of each embodiment are shown in Table 1.

[0082] Table 1.

[0083]

[0084] ***In step S1, Li:Fe:P refers to the added molar ratio of lithium, iron and phosphorus in the lithium source, iron source and phosphorus source, and the added amount of the orientation regulator is calculated based on the dry weight of lithium iron phosphate in the lithium iron phosphate slurry.

[0085] ***In step S2, the amount of carbon source added is calculated based on the dry weight of lithium iron phosphate in the lithium iron phosphate slurry, and the amount of lithium supplement added is calculated based on the dry weight of lithium iron phosphate in the lithium iron phosphate slurry.

[0086] Example 4

[0087] This embodiment adopts the method provided in Example 1 to prepare lithium ion positive electrode materials, except that in step S1, vanadium sulfate is also added to the mixing treatment I, and the added molar ratio of lithium element and vanadium element in the lithium source and vanadium sulfate is 1:0.01. Other conditions are the same to prepare lithium ion positive electrode materials.

[0088] Comparative Examples 1 to 4

[0089] Comparative Examples 1 to 4 use the method provided in Example 1 to prepare lithium ion positive electrode materials, except that the preparation conditions used in steps S1 to S3 are different, as shown in Table 2.

[0090] Table 2.

[0091]

[0092] Test Example 1

[0093] This test example is used to illustrate the microstructure of the lithium ion positive electrode material provided in the above embodiments and comparative examples. The test specifically includes:

[0094] 1. Carbon content of the carbon coating layer: The BET method was used to detect the BET area of ​​the lithium ion positive electrode material, and the carbon content of the carbon coating layer was calculated according to the following formula. The results are shown in Table 3.

[0095] Carbon content of carbon coating = m / S

[0096] Wherein, m is the mass of carbon atoms in the carbon source added in step S2, unit: g, S is the BET area of ​​the lithium ion positive electrode material, unit: m 2 .

[0097] 2. Lattice structure: (1) The test was conducted using Bruker D8 ADVANCE equipment and Cu-kα as the radiation source. The powder was poured into the sample holder using the upright method to prepare the sample, ensuring that the sample height was consistent with the sample holder. The sample test conditions included: an angle range of 10° to 80°, a step length of The dwell time for each step was 0.3 s, and the corresponding XRD pattern was obtained by testing;

[0098] (2) Use the Rietveld fitting refinement method to refine and fit the characteristic peaks representing the (200) crystal plane and the (101) crystal plane in the XRD spectrum: open the TOPAS refinement software, import the XRD spectrum obtained in the test (1) into the software, select the sample batch to be refined, first perform background subtraction, select the background fitting parameter (Background) and change the polynomial series Order setting to 4; then import the instrument parameters in the instrument parameter (Instrument) task bar; check Sampledisplacement (sample height correction) in the error correction parameter (Corrections); import the structure file of the lithium battery positive electrode material, select Sites in the structure file to set the structure parameters according to the material characteristics, select the characteristic peaks of the (200) crystal plane (about 17.2°) and the (101) crystal plane (about 20.8°) for single peak fitting, and obtain the (200) crystal plane size d 200 and (101) plane size d 101 , and the ratio Kr of the (200) crystal plane size to the (101) crystal plane size is calculated according to the following formula. The results are shown in Table 3.

[0099] Kr=d 200 / d 101

[0100] Table 3.

[0101]

[0102] It can be seen from the test results shown in Table 3 that the preparation method provided by Examples 1 to 4 of the present invention can be used to prepare a lithium ion positive electrode material including a carbon coating layer, and the ratio Kr of the (200) crystal plane size to the (101) crystal plane size of the lithium ion positive electrode material is in the range of 0.82 to 1.08.

[0103] Test Example 2

[0104] This test example is used to illustrate the time domain differential potential ratio K of the lithium ion positive electrode materials provided in the above embodiments and comparative examples. ΔV , the test specifically includes:

[0105] 1. Assembly of button cell batteries: (1) Lithium ion positive electrode material, conductive agent Super P and binder PVDF were mixed in a mass ratio of 9:0.4:0.6, and the slurry was adjusted in a degassing machine to control the viscosity of the slurry to 8000 mPa·s. Then, the slurry was evenly coated on a carbon-coated aluminum foil using an automatic coating machine to form an original electrode sheet, which was placed in a vacuum oven at 130°C for 4 hours and then placed in a blast oven at 80°C for 12 hours to obtain a test piece;

[0106] (2) Use a punching die with a diameter of 14 mm to cut out several small electrode sheets at different positions of the above test piece, select small electrode sheets with regular morphology, smooth surface and edges, weigh them with a 1 / 10,000 balance, put the weighed small electrode sheets into a vacuum drying oven, evacuate to 0.1 MPa, obtain positive electrode sheets, and store them for future use;

[0107] (3) In an inert gas glove box where the mass contents of water and oxygen are both less than or equal to 0.0005%, button cells are assembled according to the battery specifications of CR2023; wherein the negative electrode is a lithium sheet, the separator is a polypropylene film, the electrolyte solvent is a mixed solution of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, and the conductive salt is 1M lithium hexafluorophosphate. After the assembly is completed, the button cells are packaged at 800 Pa for 5 seconds to obtain button cells.

[0108] 2. Time domain differential potential ratio K ΔV Test: (1) At 25°C, the button cell was charged to 4.2 V (vs Li) at a constant current rate of 0.1C, and then the button cell was charged at a constant voltage to a cut-off rate of 0.02C at a potential of 4.2 V (vs Li), and then discharged to 2.5 V (vs Li) at a constant current rate of 0.1C to complete the necessary first cycle of charge and discharge;

[0109] (2) At 25°C, the button cell was charged at a constant current of 0.1C to a cutoff voltage of 4.2V (vs Li), and then charged at a constant voltage of 4.2V (vs Li) to a cutoff rate of 0.02C, at which point the state of charge (SOC) of the button cell was 100%;

[0110] (3) Using a battery performance tester with a potential accuracy of 0.3 mV, discharge the button cell at a constant current rate of 0.1C to 50% SOC at 25°C, let it stand for 1 hour, and record the actual open circuit potential value of the button cell, which is calculated as V0; set the rate to 1.0C for constant current pulse discharge, the pulse time is 60 seconds, and record the instantaneous potential value at 1 second, which is calculated as V 1s , record the instantaneous potential value at 18 seconds, counted as V 18s ; and calculate the K of the button cell at 25°C according to the following formula: ΔV , the results are shown in Table 4.

[0111]

[0112] Table 4.

[0113]

[0114]

[0115] From the test results shown in Table 4, it can be seen that the time domain differential potential ratio K of the button battery made of the lithium ion positive electrode material provided by Examples 1 to 4 of the present invention at 25°C is ΔV It is 2.21~3.20.

[0116] Test Example 3

[0117] This test example is used to illustrate the DCR performance of the lithium ion positive electrode materials provided in the above embodiments and comparative examples. The test specifically includes:

[0118] 1. Assembly of button-type battery: Assemble button-type batteries according to the method provided in Test Example 2.

[0119] 2. DCR performance test: (1) Perform the necessary first cycle charge and discharge on the button cell according to the method provided in Test Example 2;

[0120] (2) Using a battery performance tester with a potential accuracy of 0.3 mV, discharge the button cell at a constant current rate of 0.1C to 50% SOC at 25°C, let it stand for 1 hour, and record the actual open circuit potential value of the button cell, which is calculated as V0; set the rate to 1.0C for constant current pulse discharge, the pulse time is 60 seconds, and record the instantaneous potential value at 1 second, which is calculated as V 1s , record the instantaneous potential value at 18 seconds, counted as V 18s; and calculate the DCR calculation formula according to the following formula to calculate 1s DCR and 18s DCR respectively. The results are as follows Figure 1 And as shown in Table 5.

[0121]

[0122] Where V0 is the actual open circuit potential of the button battery, in V; V ns It is the instantaneous potential value of the button battery at the nth second of constant current pulse discharge, in V.

[0123] Table 5.

[0124]

[0125] Depend on Figure 1 As shown in the test results in Table 5, compared with the lithium ion positive electrode materials provided in Comparative Examples 1 to 4, the Kr of the lithium ion positive electrode materials provided by Examples 1 to 4 of the present invention is in the range of 0.82 to 1.08, and K ΔV In the numerical range of 2.21 to 3.20, the button cell made of it as the positive electrode material exhibits excellent DCR performance, which can effectively solve the problems of lithium ions in the lithium iron phosphate material being unable to migrate in time and the enhanced polarization phenomenon inside the material during the battery charging and discharging process, and has good practical application prospects.

[0126] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A lithium ion positive electrode material, characterized in that The lithium ion positive electrode material comprises a lithium iron phosphate material having a carbon coating layer, and the lithium ion positive electrode material has the following characteristics: The ratio Kr of the (200) crystal plane size to the (101) crystal plane size in the XRD spectrum of the lithium ion positive electrode material is 0.82 to 1.08; and, the time domain differential potential ratio K of the battery made of the lithium ion positive electrode material ΔV 2.21~3.2, K ΔV The calculation formula is as follows: Among them, V0 is the open circuit potential value measured by the battery, V 1s V is the potential value of the battery measured 1s after constant current is applied. 18s K is the potential value measured by the battery 18s after constant current is applied; ΔV The test conditions include: temperature of 24-26°C and constant current of 0.09-0.11°C.

2. The lithium ion positive electrode material according to claim 1, characterized in that In the XRD spectrum of the lithium ion positive electrode material, the ratio Kr of the (200) crystal plane size to the (101) crystal plane size is 0.82 to 1.03; Optionally, the time domain differential potential ratio K of the battery made of the lithium ion positive electrode material is ΔV It is 2.24~3.

15.

3. The lithium ion positive electrode material according to claim 1, characterized in that The general chemical formula of the lithium iron phosphate material includes LiFe x M 1-x PO4; wherein 0.98≤x<1.0; the M element is selected from one or more of Mn, F, Al, Ti, Zr, Co, Zn and V.

4. The lithium ion positive electrode material according to claim 1, characterized in that Based on the BET area of ​​the lithium iron phosphate material, the carbon content of the carbon coating layer in the lithium ion positive electrode material is 7.5-13 g / m 2 .

5. The method for preparing a lithium ion positive electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: S1, taking a lithium source, an iron source, a phosphorus source, an orientation regulator and a solvent for mixing treatment I to obtain a premixed slurry; taking the premixed slurry for high pressure hydrothermal reaction and purification treatment to obtain a lithium iron phosphate slurry; S2, taking the lithium iron phosphate slurry, the carbon source and the lithium supplement agent for mixing treatment II and drying treatment to obtain a mixed dry powder; S3, taking the mixed dry powder and sintering it at high temperature to obtain the lithium ion positive electrode material; The orientation regulator includes one or more of tetracarboxyl porphyrin, sucrose, starch, acetic acid, oxalic acid, citric acid, sodium dodecylbenzene sulfonate, glucoside and polyethylene glycol sulfate, and the added concentration of the orientation regulator is 0.4-10wt% based on the mass of the lithium source.

6. The method for preparing a lithium ion positive electrode material according to claim 5, characterized in that: In step S1, based on the mass of the lithium source, the alignment regulator includes 0.009-0.011 wt% of tetracarboxyl porphyrin, 0.049-0.051 wt% of starch, 0.29-0.31 wt% of acetic acid and 0.09-0.11 wt% of glucoside in an added concentration; Optionally, based on the mass of the lithium source, the alignment regulator includes oxalic acid at a concentration of 2.9 to 3.1 wt%, citric acid at a concentration of 0.9 to 1.1 wt%, and polyethylene glycol sulfate at a concentration of 0.049 to 0.051 wt%. Optionally, based on the mass of the lithium source, the alignment regulator includes 0.009-0.011 wt % of tetracarboxyl porphyrin, 4.9-5.1 wt % of oxalic acid, 0.9-1.1 wt % of citric acid and 0.9-1.1 wt % of sodium dodecylbenzene sulfonate.

7. The method for preparing a lithium ion positive electrode material according to claim 5, characterized in that: In step S1, the lithium source is selected from lithium carbonate and / or lithium hydroxide; Optionally, the iron source is selected from one or more of ferrous oxalate, ferrous nitrate and ferrous sulfate; Optionally, the phosphorus source is phosphoric acid; Optionally, the solvent is selected from one or more of ethylene glycol, diethylene glycol and water; Optionally, the molar ratio of lithium, iron and phosphorus in the lithium source, iron source and phosphorus source is (2.98-3.02):1:(0.97-1.03); Optionally, a supplement containing an M element is further added to the mixing process I, and the M element is selected from one or more of Mn, F, Al, Ti, Zr, Co, Zn and V; Optionally, the supplement containing the M element is selected from one or more of manganese sulfate, aluminum fluoride, titanium oxalate, zirconium sulfate, cobalt sulfate, zinc chloride and vanadium sulfate; Optionally, the molar ratio of lithium element to M element in the lithium source and the supplement is 1:(0.005-0.025); Optionally, the high pressure hydrothermal reaction has a gas pressure of 1.6 to 2 MPa, a temperature of 180 to 230° C., and a time of 2 to 5 hours.

8. The method for preparing a lithium ion positive electrode material according to claim 5, characterized in that: In step S2, the carbon source is selected from one or more of glucose, sucrose, starch, and polyvinyl alcohol; Optionally, the lithium supplement is selected from one or more of lithium carbonate, lithium hydroxide, lithium oxide, lithium gluconate, lithium citrate, lithium dihydrogen phosphate and lithium phosphate; Optionally, based on the dry weight of lithium iron phosphate in the lithium iron phosphate slurry, the added amount of the carbon source is 1 to 20 wt %, and the added amount of the lithium supplement agent is 1 to 4 wt %.

9. The method for preparing a lithium ion positive electrode material according to claim 5, characterized in that: In step S3, the high-temperature sintering atmosphere includes an inert gas and optionally carbon monoxide, the temperature is 650-780°C, and the time is 3-10 hours.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion positive electrode material according to any one of claims 1 to 4.

Citation Information

Cited By

  • Lithium iron phosphate positive electrode material, preparation method and application

    CN121123239A

  • Lithium iron phosphate cathode materials, preparation methods and applications

    CN121123239B